APPLICATIONS OF DIABETIC FOOT EXERCISE TO INCREASE FOOT SENSITIVITY IN ELDERLY WITH TYPE 2 DIABETES MELLITUS - Siti Aisah; Fika Zahrun Ni'mah (Journal of Vocational Nursing, 2023)
Introduction: Diabetes Mellitus is one of the global health emergencies. Approximately 40-59% of all people with diabetes mellitus will experience diabetic peripheral neuropathy with decreased foot sensitivity. Diabetic foot exercise can improve blood circulation, especially in the legs or lower limbs. This case study was aimed to determine the increased foot sensitivity in elderly with Type 2 Diabetes Mellitus after diabetic foot exercise. Methods: This case study design used a descriptive method with a family nursing care approach. The   case   study   will be   carried   out   at Sendangmulyo, Semarang in June 2023. There were 3 clients in the family developmental stage of the elderly with Type 2 Diabetes Mellitus who were selected using a purposive sampling technique. Inclusion criteria in this study were type 2 diabetics aged â‰¥ 60 years, female, diagnosed of diabetes > 5 years, and having controlled OADs. While the exclusion criteria were type 2 diabetics with diabetic ulcers. Clients are given foot exercises for 7 days with a duration of 30-45 minutes each. The case study instrument was 10g Retractable Monofilament with a diameter of 0.4 mm. Results:  After 7 days of intervention, there was an increased foot sensitivity, with a mean increased score on right and left foot of 0,43 and 0,33. Conclusions: Diabetic foot exercise for 7 days with a duration of 30-45 minutes can increase foot sensitivity in elderly with Type 2 Diabetes Mellitus. Increased foot sensitivity is due to peripheral blood vessel vasodilation. Diabetic foot exercise can be applied as an independent measure to prevent diabetic peripheral neuropathy